All the best lines : an informal history of the movies - Tiffin, George (London : Head of Zeus, 2013)
An informal history of the movies told through some of cinema's best-loved scenes, from the early days of Hollywood to the present day.
Keywords: Motion pictures -- History; Motion pictures -- Plots, themes, etc; Motion pictures -- Anecdotes; Dialogue in motion pictures